2021
DOI: 10.1177/23315024211036014
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Voice and Agency Among Forcibly Displaced Children and Adolescents: Participatory Approaches to Practice in Conflict-Affected Settings

Abstract: Globally, large numbers of children and adolescents are displaced by armed conflict, which poses significant threats to their mental health, psychosocial well-being, and protection. Although humanitarian work to support mental health, psychosocial well-being, and protection has done considerable good, this paper analyzes how humanitarian action is limited by excessive reliance on a top-down approach. Although the focus is on settings of armed conflict, the analysis offered in this paper applies also to the wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Afghan refugees often hold rich funds of knowledge regarding how to holistically navigate the challenges of post resettlement, much of which may be rooted in their unique culturally and spiritually informed notions of coping and healing. Peripheral adaptations can fall short in benefiting from these relevant and necessary sources of wisdom, potentially contributing to limitations in the extent to which EBI can be effective (Wessells, 2021). We join forces with other scholars who advocate for further rigorous explorations into how levels and types of cultural adaptations can impact program effectiveness and success (Taylor et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Afghan refugees often hold rich funds of knowledge regarding how to holistically navigate the challenges of post resettlement, much of which may be rooted in their unique culturally and spiritually informed notions of coping and healing. Peripheral adaptations can fall short in benefiting from these relevant and necessary sources of wisdom, potentially contributing to limitations in the extent to which EBI can be effective (Wessells, 2021). We join forces with other scholars who advocate for further rigorous explorations into how levels and types of cultural adaptations can impact program effectiveness and success (Taylor et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…These stories might involve distress and suffering, but may also be filled with beauty and resilience (Watkins, 2015, p. 330). Accompaniment involves the accompanier listening intently to what the accompanied person says, without attempting to intervene or provide solutions (Kapitan, 2023), and setting aside the ‘vertical hierarchy of expertism’ and moving instead to a ‘practice of horizontality’ (Watkins, 2015, p. 330) where the accompanier is in a position to learn from the person they are accompanying (Wessells, 2021). Freire frames these dialogues in terms of love and writes:
Dialogue cannot exist, however, in the absence of a profound love for the world and for people.
…”
Section: Accompaniment and Positionalitymentioning
confidence: 99%
“…An example of inadequacy is that the majority of psychological interventions have been primarily developed and tested for homogeneous White populations, without critical examination of the significant limitations of psychologists’ own knowledge and practices with populations who may have different priorities, preferences, core cultural beliefs, and explanatory models, with consequences for mental health utilization which is lower among refugees than the general population (Lamkaddem et al, 2014; Satinsky et al, 2019). Despite interest and alignment for refugees themselves, conspicuously few opportunities exist for indigenous and culturally relevant healing practices to be uplifted and utilized (Khairat et al, 2023; Wessells, 2021). Notably, a critical systemic review of research on Middle Eastern refugee women found that, across studies, stigma, embarrassment, and shame played a role in service utilization, and refugee women expressed a preference to utilize cultural and faith-based practices, such as prayer and social support, and traditional healing (Tahir et al, 2022).…”
Section: Dismantling Racism Through Truth-telling: Critical Reflectio...mentioning
confidence: 99%